Lifestyle transformation and reduced consumption: a transformative learning process - Magnus Boström (sozialpolitik.ch, 2022)
Overconsumption habits and structures have a huge environmental impact. The article uses a qualitative interview study of environmentally conscious Swedish citizens undertaking a lifestyle transformation process to reduce their overall consumption in the context of mass consumption society. The purpose is to emphasise the importance of a transformative learning perspective to understand pathways and challenges for transforming towards less consumerist lifestyles. The study demonstrates five mutually bolstering aspects of learning experiences in this lifestyle transformation process: 1) factual and theoretical learning; 2) practical, corporal and tacit learning; 3) personal and emotional learning; 4) social relational learning; and 5) critical learning. It stresses the importance of a social dimension including the interplay of macro, meso and micro levels.